Ordinance No. 79, § 1, ADAMS COUNTY NEWS, Jun. 14, 1899, at 2 (Ritzville, Washington). - (:unkn) unknown (My University, 1899)
Declared that all persons who carry concealed weapons, Brandish such weapons, carry weapons with intent to do bodily injury, and those who discharge firearms within the city limits are disorderly persons
Keywords: BRANDISHING; CARRY - CONCEALED; CARRY - INTENT TO COMMIT CRIME; DISCHARGE